Imagine a place : stories from middle grades educators - Carpenter, Jan Marie; Lutz, Amy; Samek, Linda; Caskey, Micki M.; Greene, William L.; Kim, Younghee M.; Casbon, Jay; Musser, Maureen (Handbook of resources in middle level education., 2017)
Imagine a place where passion for learning, authentic connection with colleagues and community, and strengths-based middle grades education thrive. Imagine places of learning and inspiration for teachers, administrators, teacher educators, and teacher candidates. Imagine a Place: Stories From Middle Grades Educators, a new anthology of teacher-written narratives, focuses on educators' stories that have the power to offer hope, ignite creativity, and provide practical ideas for middle grades teachers.Imagine a Place is filled with stories of joy, stories of relationships, and stories of finding the treasure in challenging situations that provide powerful insight into the world of teaching young adolescent learners. Along with teacher narratives, the editors of this book provide questions and exercises for thoughtful reflections on the themes and issues raised in each story as well as guidance for the reader to write his or her own account of their middle grades teaching experiences. We invite you to join these teachers in their classrooms as they reflect on their experiences with young adolescents in the place we call school.